IMPLEMENTASI PROGRAM LITERASI DALAM MENINGKATKAN KECERDASAN VERBAL LINGUISTIK SISWA DI SMP AL-FURQAN MADRASATUL QUR’AN TEBUIRENG - Galang Izhuma Refangga; Syamsuddin Syamsuddin (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The low interest in reading among students in Indonesia causes a decline in achievement in both academic and non-academic fields. Therefore, the Ministry of Education and Culture launched a program, namely the School Literacy Movement (GLS) in order to familiarize and increase students' interest in reading. And one of the schools or madrasas that carries out literacy activities at Al-Furqon Madrasatul Qur'an Middle School.This research aims to: (1) Understand the literacy program policy at Al-Furqan Madrasatul Qur'an Middle School, (2) Describe the supporting and inhibiting factors in implementing the literacy program at Madrasatul Qur'an Middle School, (3) Describe the impact of implementing the literacy program on student achievement at Al-Furqan Madrasatul Qur'an Middle School The approach used to achieve the above objectives is to use a qualitative research approach with a field study type of research. In collecting data, the author used observation, interviews and documentation methods. Meanwhile, in data analysis, the author uses qualitative descriptive analysis by reducing and displaying the data with several brief descriptions and concluding flexibly in order to answer the existing problem formulation. The results of the research show that Al-Furqan Madrasatul Qur'an Middle School has a policy in implementing literacy activities. This activity was carried out before the School Literacy Movement (GLS). Al-Furqan Madrasatul Qur'an Middle School has supporting factors for implementing literacy programs such as (a) adequate facilities (library, reading garden, reading alley, reading corner, internet connection, computer laboratory, book collection which is upgraded every year), (b ) teachers who are qualified in the field of literacy are proven by the existence of several teachers who take part in training, writing competitions and have published works, (c) students who enthusiastically take part in literacy programs and produce many works both inside and outside the madrasah. Apart from that, there are inhibiting factors, namely: the intention and stimulus that must be given to students (3) the impact of implementing the literacy program on students' verbal linguistic intelligence at Al-Furqan Madrasatul Qur'an Middle School, namely that the level of students' intelligence increases significantly. where students improve their civic intelligence. It is clear that the students have improved in virtue, dignity, ability, wisdom, emotional control, and morality since the start of this literacy program.